Review paper-Theoretical Foundations of Employee Retention of BPO’s: Exploring Key Antecedents - Rafat Fatma (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2026)
These days, keeping employees engaged and committed is crucial to the organization's strategy. For the long-term benefit of the company and its members, it is not only critical to have the greatest and most talented personnel; it is also critical to be able to retain them. This paper's goal is to examine the research papers written by different writers in order to identify the elements that affect employee retention and engagement in the workplace. This research looks at the following important predicators: work-life balance; organizational culture; employee engagement; satisfaction with performance in hiring and selection; career management; teamwork; and management support in terms of pay and benefits. Since different organizations place varying degrees of emphasis on these guidelines based on how well they fit the needs of their retention strategies, there are no set procedures that demonstrate the full scope and significance of the influence of all the aforementioned broad themes. Drawing from this comprehension of the papers; recommendations are made that provide an integrated perspective on the several approaches that companies should implement to maintain a high degree of employee engagement and retention.